Web-based Educational Game Application to Improve the Ability to Identifying the Main Idea in Indonesian Language Learning - Qonitattsani, Zirly Fiera; Sukardi (International Journal of Elementary Education, 2024)
The limited provision of innovative, interesting, and technology-based learning media can affect the running of teaching and learning activities in schools to be less than optimal, especially in Indonesian subjects. The purpose of this research is to create a web-based educational game media application to improve the ability to identify the main idea in Indonesian language subjects on learning entrepreneurship material for grade V elementary school students. This study uses a type of Research and Development research with the ADDIE research and development model. Techniques applied in data collection are test techniques through pretests and posttests, as well as non-test techniques through observation activities, interviews, data in the form of documents, and questionnaires or questionnaires. The questionnaire instrument in data collection is in the form of a rating scale that has passed testing from media experts, material experts, practitioners, and students. The sample for this research was 24 fifth-grade elementary school students. Quantitative descriptive analysis techniques and qualitative descriptive analysis are the two techniques used in this study. The data analysis process in this study uses the SPSS 29 application which includes several test processes including the normality test, homogeneity test, t-test, and N-Gain test. The results of the study obtained that the web-based educational game learning media developed is very feasible and effective to be applied to the Indonesian language learning process to improve the understanding and learning outcomes of fifth-grade elementary school.